Long-term Resilient Labour Strategies to Deal with the Economic Crisis in Europe Using Qualitative Comparative Analysis (QCA) - Martínez-Molina, Sandra; Pavía, Paula Sabater; Ferrer, Jorge Garcés (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
The crisis has had a negative impact on both European economies and labour markets with different effects among countries, raising the importance of analysing the labour market resilience. This paper seeks to identify which strategies and labour adjustments have led European labour markets to both resilient and non-resilient results by using Qualitative Comparative Analysis (QCA). The findings show two different configurations explaining 57% of the resilient cases and four configurations explaining 74% of the non-resilient cases. The results of this study revealed three important issues. First of all, the same strategy was found to have different results on labour markets. This fact stressed that the context in which different measures are imposed is a decisive factor in their success. Secondly, resilient strategies underlined the importance of â€œflexibilityâ€, by increasing temporary employment together with other conditions to escape from the crisis. Finally, the non-resilient results stress the importance of the imbalance between the flexicurity dimensions and the effect of the fall in economic activity on not being resilient in the long-term.